2015
DOI: 10.4315/0362-028x.jfp-14-574
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Shell Egg Consumption and Handling Practices: Results from a National Survey

Abstract: Numerous cases and outbreaks of Salmonella infection are attributable to shell eggs each year in the United States. Safe handling and consumption of shell eggs at home can help reduce foodborne illness attributable to shell eggs. A nationally representative Web survey of 1,504 U.S. adult grocery shoppers was conducted to describe consumer handling practices and consumption of shell eggs at home. Based on self-reported survey data, most respondents purchase shell eggs from a grocery store (89.5%), and these egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Also, in previous studies, samples were presented as boiled eggs. Recent data suggest that US consumers are as likely or more likely to prepare eggs broken out of the shell (e.g., by scrambling or frying) than by boiling in the shell ( 14 ). In this study, we revisit the hypothesis that sensory differences between eggs are not perceptible when hulless oats are used to replace corn or wheat in layer diets, and explore whether it holds under the conditions of a more rigorous test using a broken-out sample preparation method and a larger, untrained consumer panel.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in previous studies, samples were presented as boiled eggs. Recent data suggest that US consumers are as likely or more likely to prepare eggs broken out of the shell (e.g., by scrambling or frying) than by boiling in the shell ( 14 ). In this study, we revisit the hypothesis that sensory differences between eggs are not perceptible when hulless oats are used to replace corn or wheat in layer diets, and explore whether it holds under the conditions of a more rigorous test using a broken-out sample preparation method and a larger, untrained consumer panel.…”
Section: Introductionmentioning
confidence: 99%
“…Cleanliness seems to be a factor that may determine egg purchasing. In an online survey conducted in the United States, 86% of the respondents indicated that they checked if eggs are clean and not cracked before acquiring them (Kosa, Cates, Bradley, Godwin, et al., 2015). Consumers in Ghana considered cleanliness as one of the most important parameters preceded by size and price (Ayim‐Akonor & Akonor, 2014).…”
Section: Consumer Food Journey: Where and How Risk May Occurmentioning
confidence: 99%
“…In studies from the United States, 48.1% of the participants self‐reported washing their hands with soap and water after cracking a raw egg (Kosa, Cates, Bradley, Chambers IV, et al., 2015; Kosa, Cates, Bradley, Godwin, et al., 2015), whereas 15% and 17% demonstrated “a proper hand washing” (Maughan et al., 2016) after handling raw eggs for fried eggs and for scrambled eggs, respectively. In the self‐reporting study, women and individuals with a high school education or less were more prone to washing their hands after touching eggs than other groups.…”
Section: Consumer Food Journey: Where and How Risk May Occurmentioning
confidence: 99%
“…For dishes that include raw or undercooked eggs, such as ice cream, and salad dressing, it is recommended that pasteurized egg products be used [ 9 , 10 ]. Those same sources recommend that egg dishes such as casseroles be cooked until the internal temperature reaches 71 °C, although consumers have indicated that they do not use thermometers for egg dishes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%